MANAJEMEN PENINGKATKAN MUTU PENDIDIKAN BERBASIS MADRASAH - simatupang, wandana; Syahputra, Refi; nasution, Baginda (Ekonomi : Jurnal Perbankan Syariah, 2025)
Research purposes; This research elaborates the theory of educational quality with educational management theory which is then oriented towards improving the quality of education in madrasah institutions by integrating several regulations regarding the parallels between national (general) education and madrasah (religious) education. Approach Method; The method used is literature study with descriptive analysis techniques. The data used is quantitative data. Analyzing data by reducing data, presenting data, and concluding and checking research results continuously in the research process. Results and Conclusions; (1) Islamic education is the same and equivalent to national education with the issuance of SKB 3 Ministers on March 24 1975, in an effort to overcome the backwardness of religious education. (2) The integration of madrasas into the National Education system is strengthened by PP No. 28 of 1990 and Decree of the Minister of National Education No. 0478/U/1992 and No.054/U/1993. Minister of Religion Decree No. 368 and 369 of 1993 concerning the implementation of MI and MTs. MA PP level. No. 29 of 1990, Minister of National Education Decree no. 0489/U/1992 and Decree of the Minister of Religion No. 370 of 1993. (3) School Based Management (SBM). The English terminology is called SBM, which is a management model that provides autonomy or independence to madrasas in encouraging participatory decision making that directly involves all madrasah residents in accordance with service standards set by the Central, Provincial, Regency and City Governments.